Modeling HIV evolution from SIV using a humanized mouse model - Curlin, James, author; Schmitt, Kimberly, author; Remling-Mulder, Leila, author; Stenglein, Mark, author; O'Connor, Shelby, author; Marx, Preston, author; Akkina, Ramesh, author (Colorado State University. Libraries, 2017)
Human Immunodeficiency Virus (HIV) is believed to have arisen in humans as a result of multiple independent cross-species exposures to Simian Immunodeficiency Viruses. Here the serial passaging of SIV in humanized mice across several generations recapitulates the genetic changes that make have facilitated such cross-species transmissions. Viral adaptation to the hu-mice was determined via qRT-PCR analysis of plasma viral loads and observation of CD4+ T-cell depletion. SIVs at various stages of adaptation from different generations were analyzed through Next Generation Sequencing (NGS). Many non-synonymous mutations were observed across each passage that may be responsible for improved cross-species transmission and adaptation.
076 - James Zachary Curlin
Keywords: SIV; HIV; humanized mice; viral evolution